Hybrid Bearing with Actively Adjustable Radial Gap of Gas Foil Bearing. (2015) - Polyakov, Roman; Bondarenko, Maxim; Savin, Leonid
Abstract: The article presents the design and operation principle of a hybrid bearing with actively adjustable radial gap of a gas foil bearing. The hybrid bearing is a combination of a ball bearing and gas foil bearing with speed separation. Electromagnetic coils are placed on the bearing housing, two for each foil. Such a construction allows to control the deformation of the foils by applying voltage to the coils. The article also presents a general approach to mathematical model the control process in such bearings. The main purpose of the control system is to reduce vibrations in the rotor system by means of controlling dynamic characteristics of the gas foil bearing.